2000
DOI: 10.4315/0362-028x-63.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Gut Mucosa Morphology and Microflora Changes in Malnourished Mice after Renutrition with Milk and Administration of Lactobacillus casei

Abstract: Nutrition plays a key role in maintaining the balance of the intestinal microflora. Malnutrition disturbs the ecological barrier and induces histological damage. We evaluated modifications induced by renutrition with nonfat milk (NFM) and Lactobacillus casei administration (for 2 days) on the bacterial gut population and structural and ultrastructural gut modifications in malnourished mice. Balb/c mice suffering from a malnutrition process immediately after weaning (for 21 days) were divided into four groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…The gut mucins afford the first line of defence against bacteria and are one of the main constituents of the gut barrier (Allori et al, 2000). Mucins are produced in the gut by specialized goblet cells and an enhanced presence of goblet Other investigators (Sherman et al, 1985) have shown that chronic protein depletion or protein-energy undernutrition decrease the number of goblet cells and mucin synthesis in the proximal small intestine of rodents and piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut mucins afford the first line of defence against bacteria and are one of the main constituents of the gut barrier (Allori et al, 2000). Mucins are produced in the gut by specialized goblet cells and an enhanced presence of goblet Other investigators (Sherman et al, 1985) have shown that chronic protein depletion or protein-energy undernutrition decrease the number of goblet cells and mucin synthesis in the proximal small intestine of rodents and piglets.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important functions of the gut is to prevent lumen pathogenic bacteria and toxins from reaching the systemic circulation, organs and internal tissues (Allori et al, 2000). The gut mucins afford the first line of defence against bacteria and are one of the main constituents of the gut barrier (Allori et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between malnutrition and gastrointestinal microbiota has been intensively studied in malnourished children, whose status is always complicated with deficiencies of other nutrients and different infections (14,15), and in experimental animals in which malnutrition was induced in different ways (9,11,16). However, there have been limited studies investigating the effects of a definite qualitative or quantitative dietary protein deficiency on the gastrointestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that probiotics estimulate cell proliferation of the immune system associated to the intestinal mucosa (Erickson and Hubbard 2000, Cano and Perdigón 2003, Villena et al 2006, De Souza et al 2007, Dewan et al 2007, kaburagi et al 2007, Pitsouni et al 2009), which may contribute to the control of infections, as well as to their prevention in the case of diseases derived from nutritional deficiency. On the other hand, there are few studies that evaluated the action of probiotics on the intestinal morphology of malnourished animals, and were mostly restricted only to the study of the mucosa (Allori et al 2000, Cano et al 2002, Dock et al 2004a, b, Dock-Nascimento et al 2007. A single study examined the different strata of the intestinal wall by examining only the small intestine (J.F.…”
Section: Introductionmentioning
confidence: 99%